2017
DOI: 10.13057/tropdrylands/t010104
|View full text |Cite
|
Sign up to set email alerts
|

Yield performance of eight mungbean (Phaseolus radiatus) genotypes in two locations in Manggarai District, East Nusa Tenggara, Indonesia

Abstract: Abstract. Mau YS, Madu1VFY, Ndiwa ASS, Adar D, Gandut YRY. 2017 District, East Nusa Tenggara,. The objective of this study was to elucidate yield performance of eight mungbean genotypes at two locations in Manggarai District, East Nusa Tenggara Province. A Randomized Block Design was employed consisting of 8 treatments, each was 3 replicates. The assigned treatments were eight mungbean genotypes consisted of one local cultivar and seven Indonesian released superior varieties. Observed variables included yield … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 2 publications
(2 reference statements)
0
5
0
Order By: Relevance
“…Similarly, seed size in improved mungbean genotypes ranged from 5.8-8.0 g in a study undertaken in West Timor of Perak and Watubaur, except for the local cv. Manggarai (3.1 g in Perak and 3.6 g in Watubaur) [25,26]. The drought treatment did not affect 100-seed weight at the Aileu site due to the early rain interruption; however, drought significantly affected seed size at the Hera site.…”
Section: Source Of Variationmentioning
confidence: 91%
See 1 more Smart Citation
“…Similarly, seed size in improved mungbean genotypes ranged from 5.8-8.0 g in a study undertaken in West Timor of Perak and Watubaur, except for the local cv. Manggarai (3.1 g in Perak and 3.6 g in Watubaur) [25,26]. The drought treatment did not affect 100-seed weight at the Aileu site due to the early rain interruption; however, drought significantly affected seed size at the Hera site.…”
Section: Source Of Variationmentioning
confidence: 91%
“…Seed production at the Hera site was generally higher than at the Aileu site. At the Hera site, mungbean had the highest seed yield (3.14 t/ha), well above that of the Vima genotype grown in the lowland area of Manggarai, East Nusa Tenggara (2.42 t/ha) [25]. Drought reduced plant growth and development, including yield components.…”
Section: Source Of Variationmentioning
confidence: 91%
“…Significance of G×E interaction on mungbean was reported for days to first flowering, days to 80% maturity (Waniale et al, 2014), pod weight per plant (Mau et al, 2017;Waniale et al, 2014), and grain yield per plant (Baraki et al, 2020;Ullah et al, 2012). Waniale et al (2014) and Mau et al (2017) reported different results on the effect of G×E interaction for plant height at harvest and 100-seed weight. The study of G×E interaction on harvest period could benefit mungbean breeding programs to develop short harvest period varieties, as well as to identify suitable environments for obtaining a short harvest period.…”
Section: Core Ideasmentioning
confidence: 99%
“…(2014) and Mau et al. (2017) reported different results on the effect of G×E interaction for plant height at harvest and 100‐seed weight. The study of G×E interaction on harvest period could benefit mungbean breeding programs to develop short harvest period varieties, as well as to identify suitable environments for obtaining a short harvest period.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation